Nature-inspired materials: emerging trends and prospects - Katiyar, Nirmal Kumar; Goel, Gaurav; Hawi, Sara; Goel, Saurav (Springer Nature, 2021)
The term ‘Nature-inspired’ is associated with a sequence of efforts to understand, synthesise and imitate any natural object or phenomenon either in the tangible or intangible form which allows us to obtain improved insights into nature. Such inspirations can come through materials, processes, or designs that we see around. Materials as opposed to processes and designs found in nature due to being tangible can readily be used without engineering efforts. One such example is that of an aquaporin which is used to filter water. The scope of this work in Nature-inspired materials is to define, clarify and consolidate the current understanding by probing new insights in the recent developments by reviewing examples from the laboratory to industrial scale while highlighting newer opportunities in this area. A careful analysis of the “nature-inspired materials” shows that they possess specific functionality that relies on our ability to harness peculiar electrical, mechanical, biological, chemical, sustainability or combined gains.
Keywords: Bioinspired material; Design spiral; Biomimetic; Hierarchical structure; Biomimicry; Nature inspired